2001
DOI: 10.1002/fut.2202
|View full text |Cite
|
Sign up to set email alerts
|

Volume and Volatility Surrounding Quarterly Redesignation of the Lead S&P 500 Futures Contract

Abstract: microstructure of the futures exchange rather than new information or underlying volatility conditions. The event thus offers us an opportunity to examine how volatility responds to noninformation-based exogenous changes in volume. This study examines the volatility behavior of nearby and next out S&P 500 futures contracts on the 10 days surrounding quarterly redesignation of the lead contract. Our model measures possible changes in (a) the level of volatility and/or (b) the association between volume and vola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…It proves that the option trading volume can indeed reflect the future market volatility. The results coincide with the findings in Jayaraman et al (2001), Kawaller et al (2001), Poteshman (2006), andFung (2007). As the empirical results of the open interest are not the same as those of the option trading volume, the information covered in the option trading volume may have included the information set covered in the open interest.…”
Section: Inclusion Of the Option Market Informationsupporting
confidence: 80%
See 1 more Smart Citation
“…It proves that the option trading volume can indeed reflect the future market volatility. The results coincide with the findings in Jayaraman et al (2001), Kawaller et al (2001), Poteshman (2006), andFung (2007). As the empirical results of the open interest are not the same as those of the option trading volume, the information covered in the option trading volume may have included the information set covered in the open interest.…”
Section: Inclusion Of the Option Market Informationsupporting
confidence: 80%
“…On the contrary, if they predict future stock prices to be on the downward trend, they would tend to buy put options or sell call options in order to make profits. Jayaraman et al (2001), Kawaller et al (2001), Pand and Poteshman (2006), and Fung (2007) found that the trading volume and open interest of option markets possess the explanatory power regarding the future volatility of stock prices. The trading volume and open interest of option markets may reflect investors' expectations of future movement in stock markets.…”
Section: The Research Modelsmentioning
confidence: 99%
“…In a similar study, Kawaller, Koch, and Peterson (2001) document the microstructure changes in the S&P 500 futures contract as it switches from next-to-expire (lead) to second-to-expire (back) month contract. These authors find dramatic changes in volume when the contract moves from lead to back.…”
Section: Introductionmentioning
confidence: 94%
“…As pointed out by Kawaller et al (2001), empirical evidence of an inverse relation between the two variables is rare in the literature, and it contrasts sharply with the widely held perception that the two are positively related (see also Daigler and Wiley, 1999). Wang (2007) argues that foreign purchases tend to lower volatility, especially in the …rst few years after market liberalization when foreigners are buying into local markets.…”
mentioning
confidence: 95%
“…Kawaller et al (2001) argue that an increase in such noninformation-based trading mitigates the imbalances between liquidity suppliers and liquidity demanders by enhancing the market's capacity to absorb the information-induced trading. Accordingly, all else being equal, a marketplace with a larger population of liquidity providers (or a larger capacity to absorb demands for liquidity) will be less volatile than one with a smaller population, and vice versa (Kawaller et al, 2001). …”
mentioning
confidence: 99%